Brown adipose tissue-derived extracellular vesicles regulate hepatocyte mitochondrial activity to alleviate high-fat diet-induced jawbone osteoporosis in mice - Zhang, Kai; Zhang, Sha; Deng, Guorong; He, Guangxiang; Yuan, Yuan; Fu, Yu; Liu, Yihan; Gong, Zhen; Kong, Liang; Zheng, Chenxi (Frontiers in Endocrinology, 2025)
BackgroundLipid metabolic disorder (LMD) serves as a systemic driver of osteoporosis (OP), with jawbone osteoporosis (JOP) representing a clinically significant yet underexplored complication. Current clinical treatments for JOP remain suboptimal, highlighting the need for innovative approaches. The use of metabolic regulators represents a promising therapeutic strategy for OP management. While brown adipose tissue-derived extracellular vesicles (BEV) exhibit metabolic regulatory potential, their capacity to mitigate LMD-associated OP remains unclear.MethodsA high-fat diet (HFD)-induced LMD mouse model was established to identify the JOP phenotype through micro-computed tomography (micro-CT) and transcriptomic profiling. BEV isolation was optimized using liberase enzyme-enhanced differential centrifugation, with in vivo tracking confirming biodistribution. In vitro, BEV effects on hepatocytes were assessed with triglyceride (TG) content, free fatty acid (FFA) levels, and mitochondrial function. The additional benefits of BEV on the osteogenic microenvironment were evaluated via AML12/MC3T3-E1 indirect co-culture under high-lipid conditions. Dual therapeutic effects of BEV on LMD and JOP in vivo were validated through metabolic phenotyping, micro-CT and histomorphometry analysis.ResultsSixteen weeks of HFD successfully induced typical LMD and JOP manifestations in mice. Transcriptomic sequencing revealed downregulation of osteogenic-related genes concomitant with upregulation of lipid metabolism-associated genes in the jawbone of LMD mice. In vivo tracking showed the exogenous BEV predominantly accumulated in the liver rather than the jawbone. BEV treatment significantly reduced intracellular TG and FFA content in hepatocytes, while enhancing osteogenic activity of MC3T3-E1 cells through indirect co-culture. Mitochondrial analyses revealed that BEV effectively increased the proportion of active mitochondria, reduced reactive oxygen species (ROS) generation rate, and enhanced oxygen consumption rate (OCR) in hepatocytes. Biochemical assay and metabolic cage testing showed a lower systemic lipid content level along with improved fat utilization and thermogenesis capacity in BEV-treated mice. Micro-CT and immunofluorescence staining further confirm significant improvements in the jawbone of BEV-treated mice regarding bone volume fraction, trabecular number, trabecular thickness, trabecular separation, and RUNX2 expression.ConclusionThis study establishes LMD as a crucial driver factor in JOP and identifies BEV-mediated mitochondrial transferring in hepatocytes as a therapeutic strategy for LMD-related JOP.